Late ocular manifestations of systemic acquired toxoplasmosis-an integrative - literature review (Research, Society and Development, 2022)
Toxoplasmosis is a disease of infectious origin caused by the protozoan Toxoplasma gondii, and is responsible for several systemic manifestations, following a mild to severe clinical picture of fever, muscle pain, lymph node enlargement, neural involvement and ocular lesions. The ocular toxoplasmosis is responsible for generating an involvement of the macula, the optic nerve, the posterior uvea, generating posterior uveitis, and mainly retinochoroiditis. Toxoplasma is responsible for 50% of the cases of uveitis in Brazil. Therefore, this article aims to review the literature about the main ocular manifestations of systemic toxoplasmosis, focusing on prevalence, incidence, signs and symptoms, and main methods of approach. This is an integrative literature review, and the following databases were used for the research: PUBMED, SCIELO and BVS. The screening process had the following inclusion criteria: articles that answered the guiding question, in English, Portuguese, or Spanish, and between 2017 and 2021. After the searches, a total of 12 articles were obtained for review. Toxoplasma gondii is responsible for the secondary granulomatous inflammatory process in the choroid, and, after the acute phase, a chorioretinal scar with a white center and pigmented edges can be presented as a complication, with the main ocular manifestations being: retinochoroiditis, papillitis, neuroretinitis and scleritis. As a consequence of this ocular trophism, toxoplasma can cause a reduction in visual acuity, mostly less than or equal to 20/200, evolution to partial visual loss or blindness, presence of floaters, increased intraocular pressure, photophobia, hyperemia, simulating conjunctivitis, and visual clouding. The main population affected is the low socioeconomic development and low education associated with a higher risk of exposure to the etiologic agent. Therefore, this study reaffirms the need to continue with new studies in order to prevent diseases and promote health based on the endemicity of each region of the country, promoting integral health care and generating quality of life for these patients.